(untitled) (Physical Education, Health and Social Sciences, 2025)
Background: Postoperative problems affect four percent of surgery patients and may be more common in obese persons. It is the second most common cause of death in the United States. Obese patients are more likely to have postoperative respiratory failure than cardiac complications from surgery under general anesthesia. Objective: The objective of this study is to recognize and decrease post-operative pulmonary complications in obese patients. And also decrease the hospital stay and enhance recovery. Methodology: Study included 60 patients. All these patients had a BMI of greater than 30. All these patients had a preoperative pulmonary function test and all these patients underwent a surgery under general anesthesia. Most of these patients develop post-operative pulmonary complications. Most common complications include pneumonia, respiratory failure and atelectasis. Results: Obesity increases the risk of respiratory problems after surgery, with pneumonia and respiratory failure being the most common complications. These complications can lead to longer hospital stays, higher morbidity, and increased medical expenses. Conclusion: Following surgery, obesity raises the risk of respiratory issues; the most frequent complications are pneumonia and respiratory failure. Longer hospital stays, greater morbidity, and higher medical costs are the results of these complications. Prioritizing respiratory care and using a multidisciplinary team approach can help lower these complications and enhance patient safety and quality of life. To improve respiratory outcomes, future research should concentrate on enhancing risk prediction and creating individualized treatments.